Tramadol in seized drugs containing non-pharmaceutical fentanyl: Crime lab data from Ohio, USA. (2022) - Ruhter, Lance; Juhascik, Matthew; Watson, Jennifer; Sweeney, Kaylin; Daniulaityte, Raminta
Abstract: Introduction: Non-pharmaceutical fentanyl and related drugs (NPF) have contributed to increases in drug-related overdose mortality in the U.S. More data are needed to track the shifting composition of fentanyl-containing drug mixtures. The key aims of the study are to characterize the crime lab data from Montgomery County, Ohio on the increased cases of seized drugs containing mixtures of NPF and tramadol. Methods: Crime lab data on seized drugs in Montgomery County, Ohio (2015 - 2020) were analyzed to extract information on cases that tested positive for NPF and tramadol. Descriptive statistics are provided to characterize NPF/tramadol mixtures in terms of the quantity, weight, form of the drug seized (powder, tablet, capsule, residue), and the types of fentanyl analogs and other drugs identified. Results: In December 2017, the first case of NPF/tramadol mixture was identified in the amount of 0.2 g. Subsequently, cases containing NPF/tramadol increased significantly to 149 cases in 2018, 102 in 2019, and 134 in 2020. The total yearly amounts of seized NPF/tramadol mixtures increased to 373.27 g in 2018, 2, 601.82 g in 2019, and 13, 487.62 g in 2020. The majority (72.6%) of the cases were in powder form. There were 15 other drugs identified along with fentanyl with tramadol mixtures, including heroin (38.8%), 5.7% cocaine (5.7%), and methamphetamine (4.9%). Conclusions: The addition of tramadol to NPF may be viewed as a harm mitigation strategy but contributes to the overall unpredictability of the illicit drug supply. According to Ohio legal statutes, identification of schedule IV drugs such as tramadol with fentanyl (schedule II) may provide a reduction in drug-related charges from a felony to a misdemeanor. More research is needed to characterize potential sources of tramadol in NPF-containing drugs.